Assessment of Suicide Risks During the First Week Immediately After Discharge From Psychiatric Inpatient Facility - Madsen, Trine; Egilsdottir, Eybjørg; Damgaard, Chanette; Erlangsen, Annette; Nordentoft, Merete (Frontiers in Psychiatry, 2021)
Background The suicide rate in first week after psychiatric discharge is alarmingly high. Although a risk assessment prior to discharge is standard praxis, it can be difficult to take into consideration the obstacles that patient will meet once discharged. A follow-up-visit during the first week after discharge is an opportunity to reevaluate whether a person may be at risk of suicide. Aim To determine how many patients, of those who were assessed, were evaluated to be at elevated risk of suicide during the first week after psychiatric discharge and secondarily to identify predictors of this and predictors for receiving a follow-up visit during first week after discharge. Methods All patients discharged between March 1st 2018 to January 17th 2019 were offered a home visit including a systematic risk assessment. Socio-demographics and clinical variables were obtained from medical records and logistic regression analyses were used to identify predictors of a higher suicide risk assessment as well as receiving a follow-up visit. Results Information from 1905 discharges were included. Of these, 1052 were seen in follow-up meetings. Risk assessments was conducted in a total of 567 discharge procedures, of which 28 (5%) had an elevated risk of suicide. A history of suicide attempt, suicide risk having been the reason for admission, a first diagnosis of a psychiatric disorder was associated with an elevated risk of suicide after discharge.. Conclusion Follow-up visits could serve as an important tool to identify people who were overlooked at discharge or exposed to severe stressors after discharge.